The Effectiveness of Simulation in Education 4.0: Application in a Transesophageal Echocardiography Training Program in Malaysia - AwangHarun, Sakinah; Md Hashim, Noorjahan Haneem; Kadiman, Suhaini (Frontiers in Surgery, 2022)
Introduction: A Malaysian Higher Education Provider has applied a technology as part of its pedagogical approach, in alignment with Education 4.0. The use of simulation, which aligns with the principles of Education 4.0, employs digital technologies and supports learning by bridging the classroom and the clinical areas. We report the effectiveness of learning in our program that utilizes multimodal pedagogy; interactive lectures, pre-recorded video lectures, simulation and hands-on supervised clinical sessions, using the program’s cumulative assessment data. Methodology: This program evaluation is based on Kirkpatrick’s framework. End-points for learning (Kirkpatrick level 2) was analyzed based on improved overall post-test theoretical and clinical assessment performance. Quantitative data analysis of theoretical pre-test, theoretical post-test, clinical assessment and post-test scores were performed to compare cohorts. Results: The performance of 19 trainees, over six cohorts from 2012- 2019 were analyzed. All our trainees had equal opportunities learning using the multimodal pedagogy including a simulator. The analysis of pre- and post- theoretical test scores showed a significant improvement in the mean scores (pre-test 48.7 % (±SD 9.0), post-test 64.1% (±SD11.5); p≤0.001). 19 out of 21 trainees completed the clinical assessment and case presentation satisfactorily. Conclusion: The Kirkpatrick framework served as a useful framework to perform the evaluation of the TEE program. The significant improvement in post-test scores, when compared with pre-test scores, suggest that the program is effective with regards to learning. Simulation, as part of a multimodal pedagogy, has proven an added value to our training program, and this was reflected by improvement in the clinical assessment scores when compared to the pre-test scores. This is aligned with the concept of technology-enhanced learning in Education 4.0, where simulation in TEE training is applicable in the Malaysian context.